Non-destructive quality assessment of bio-engineering parts using Industrial Micro X-ray Computed Tomography: a review - Rathore, Jitendra Singh; Saxena, Prateek (Elsevier, 2021)
Bio-engineering parts are widely used in hearing aid applications, dental applications, inhalation therapy blends, etc. Conventional tactile measurement techniques offer a limitation in the quality assessment of such parts due to the complex shape of the part and also due to their inability to measure internal features in a three-dimensional space. Industrial micro X-ray computed tomography (>μXCT) is a robust characterization technique designed to maintain part quality, facilitate precision manufacturing, and reduce material waste due to part rejection. This paper highlights the limitations and challenges of conventional measurement techniques in the assessment of the quality of bio-engineering components. Capabilities of μXCT are presented and its application in the bio-engineering sector is discussed in this work.
Keywords: Precision manufacturing; Non destructive technique; Quality control; Bio-engineering; Micro X-ray computed tomography